Attention bias toward threat is associated with exaggerated fear expression and impaired extinction in PTSD - Fani, N. (2011)
BACKGROUND: Post-traumatic stress disorder (PTSD) develops in a minority of traumatized individuals. Attention biases to threat and abnormalities in fear learning and extinction are processes likely to play a critical role in the creation and/or maintenance of PTSD symptomatology. However, the relationship between these processes has not been established, particularly in highly traumatized populations; understanding their interaction can help inform neural network models and treatments for PTSD. METHOD: Attention biases were measured using a dot probe task modified for use with our population; task stimuli included photographs of angry facial expressions, which are emotionally salient threat signals. A fear-potentiated startle paradigm was employed to measure atypical physiological response during acquisition and extinction phases of fear learning. These measures were administered to a sample of 64 minority (largely African American), highly traumatized individuals with and without PTSD. RESULTS: Participants with PTSD demonstrated attention biases toward threat; this attentional style was associated with exaggerated startle response during fear learning and early and middle phases of extinction, even after accounting for the effects of trauma exposure. CONCLUSIONS: Our findings indicate that an attentional bias toward threat is associated with abnormalities in ‘ fear load ’ in PTSD, providing seminal evidence for an interaction between these two processes. Future research combining these behavioral and psychophysiological techniques with neuroimaging will be useful toward addressing how one process may modulate the other and understanding whether these phenomena are manifestations of dysfunction within a shared neural network. Ultimately, this may serve to inform PTSD treatments specifically designed to correct these atypical processes.